Szata graficzna polskojęzycznych edycji W pustyni i w puszczy Henryka Sienkiewicza - Rogoż, Michał (Acta Universitatis Lodziensis. Folia Librorum, 2013)
The novel by Henryk Sienkiewicz, published in 1911, has been on school reading lists and enjoyed great popularity since the beginning, a proof of which can be seen from the number of over 150 reprints. The work has been a rewarding object for graphic interpretations due to its target reader, its exotic themes typical for a tale of adventures, and the spectacular adventures of the characters. Unsurprisingly, the novel has been illustrated by almost 30 artists. Some editions were adorned with motion picture stills. The greatest number of editions featured illustrations by Szymon Kobyliński, characterized by a great deal of realism: prior to creating them, the artist meticulously collected information on Africa’s natural world and ethnography. The artwork of such recognized artists as Marek Rudnicki, Jerzy Srokowski, Jan Marcin Szancer or Ewa Bogucka-Pudlis also gained considerable popularity. The artists usually aimed at originality, which resulted in the creation of formally and stylistically varied artistic concepts. In the already published editions, one notes the prevalence of drawings and paintings over the rare use of new computer graphics. The development of printing technologies has clearly contributed to the increased number of editions with color illustrations, however, it has not increased the artistic level of newer creations. Within the past few years, a certain regress could be observed as far as novelty and originality of concept is concerned.